How do positive and negative emotions influence children’s and adolescents’ arithmetic performance? - Nurit Viesel-Nordmeyer; Patrick Lemaire (PLoS ONE, 2025)
This study is the first to investigate how negative and positive emotional states influence children’s arithmetic performance and age-related differences therein. Children aged 8–14 (n = 149) were asked to verify true/false, one-digit addition problems (i.e., 8 + 2 = 10. True? False?) which were superimposed on emotionally negative, positive, or neutral pictures. The main results showed that (a) both positive and negative emotions impaired children’s arithmetic performance, (b) deleterious effects of negative emotions were larger than those of positive emotions, (c) effects of emotions were modulated by the type of (true/false) problems, (d) effects of emotions on current trials were influenced by emotions on immediately preceding trials, and (e) effects of emotions as well as their trial-to-trial modulations changed with children’s age. These findings have important implications for further our understanding of effects of emotions in children’s arithmetic and how these effects change as children grow older.